Comparison of School Anxiety among High School Students in Bilingual, Talented, and Public Schools in Shiraz, 2020 - Mahboubeh Yarmahmoudi; Habib Hadianfard (Shiraz University of Medical Sciences, 2021)
Background: In all societies, anxiety, as a part of every human being's life, is considered as an appropriate and consistent response. Anxiety in a balanced and constructive level makes us work hard and timely, thereby making our lives longer and more fruitful. One of the contexts where anxiety could be highly harmful so much is school settings since students are vulnerable to this issue and it could impair their education. This research aimed to compare school anxiety among male and female high school students in bilingual, talented, and public schools in Shiraz, Iran. Method: We conducted this cross-sectional study to compare school anxiety among male and female high school students in bilingual, talented, and public schools of Shiraz, Iran in 2020. To this end, 725 third-grade high school students with the mean age of 17.12±0.4 from bilingual (N=95, boys=40, girls=55), talented (N=260, boys=100, girls=160), and public schools (N=370, boys=170, girls=200) were selected via a two-stage sampling method out of the statistical population with Cochran's formula. First, random schools were chosen, then, random classes were selected to collect data from volunteer students. Subsequently, among the students of these schools, 725 students were randomly selected in the second stage. The students filled out the school anxiety questionnaire and the results were analyzed with ANOVA using SPSS version 24. Results: School anxiety in bilingual schools was found to be significantly lower than that in public schools (P=0.001). In addition, school anxiety in talented schools was significantly lower than that in public schools (P=0.001), yet no differences were observed between the talented schools and bilingual schools (P=0.09). The means of school anxiety of the subjects were respectively 103.21±13.72 for public high schools, 86.32±19.68 for talented schools, and 84.45±12.73 for bilingual schools. Conclusions: These findings are up to an extent consistent with those of previous studies. There was a meaningful difference between the scores of anxiety and depression; in addition, talented students, owing to the learning of selfregulatory skills in gifted schools, had a better mental health level than those at ordinary schools. On the other hand, it seemed though the pressures of the educational system at ordinary schools, different educational, cultural, ideological, and family issues of the students and their different learning capabilities were the reasons behind their anxiety. This difference was significant in three scales of anxiety, depression, and physical symptoms.